We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-5
258
1
avatar+-19 

1. y = 2x^2 + x - 1

    y = -x - 3

 

2. y = -2x^2 - 2x + 3

    y = 7/2

 Apr 17, 2018
edited by GAMEMASTERX40  Apr 17, 2018
edited by GAMEMASTERX40  Apr 17, 2018
edited by GAMEMASTERX40  Apr 17, 2018
edited by GAMEMASTERX40  May 11, 2018
 #1
avatar+10401 
+1

1. y = 2x^2 + x - 1

    y = -x - 3

 

2. y = -2x^2 - 2x + 3

    y = 7/2

 

laugh

 Apr 18, 2018

12 Online Users

avatar
avatar